Ethnomathematics in Traditional Food: Enhancing Mathematical Literacy in Early Childhood - Jasmani, Jasmani; Suryana, Dadan; Yaswinda, Yaswinda; Mahyuddin, Nenny (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the integration of ethnomathematical concepts found in traditional West Sumatran food and their influence on the mathematical literacy skills of children aged 5-6 years. Employing a quasi-experimental pretest-posttest control group design, the research aimed to compare mathematical literacy outcomes before and after ethnomathematics-based learning interventions. A purposive sample of 12 kindergarten students from Koto Besar was assessed using structured observation sheets, and data were analyzed with SPSS 22.0. Results showed significant improvements in mathematical literacy, with pretest scores ranging from 11 to 16 and posttest scores from 20 to 30, indicating a score increase of 7 to 14 points. Normality and homogeneity tests confirmed the data's validity. The findings emphasize the effectiveness of using traditional food in teaching mathematical concepts, making them more relatable and engaging for young children while preserving cultural heritage. The study also highlights active participation and enhanced comprehension among children through culturally contextualized learning. Limitations include the small sample size and short intervention period, which may affect generalizability. Future research should involve larger samples and longer durations to confirm these findings and explore broader educational implications. Integrating ethnomathematics through traditional foods presents a promising strategy for improving mathematical literacy and cultural awareness in early childhood education.